2003
DOI: 10.1111/j.0008-3658.2003.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Disabilities, gender and employment: social exclusion, employment equity and Canadian banking1

Abstract: People with disabilities, especially women, suffer from appallingly high rates of poverty, and paid work is frequently cited as a primary route out of poverty. I draw on feminist analyses of work and disability studies to reflect on the Canadian federal government's Employment Equity Act. I use the example of the ‘Big Six’ banks to investigate the numerical representation and occupational distribution of women and men with disabilities compared to their counterparts without disabilities. However, social justic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…They represented 43.3% of all workers employed with 520 of employers covered under the EE legislation in 2006 (HRSDC, 2007: 12, 6). England (2003) analyzed the numerical representation of women and disabilities status in the "Big Six" banks and found that women with disabilities accounted for 1.3% of the labour force employed by the banks in 1981, which increased minutely to 1.4% in 2001. A principal reason for concern over occupational segregation is that it is generally seen as an important reason for the continuing differences between the average wages of men and women (Anker, 1998).…”
Section: Occupational Segregation Of Womenmentioning
confidence: 99%
“…They represented 43.3% of all workers employed with 520 of employers covered under the EE legislation in 2006 (HRSDC, 2007: 12, 6). England (2003) analyzed the numerical representation of women and disabilities status in the "Big Six" banks and found that women with disabilities accounted for 1.3% of the labour force employed by the banks in 1981, which increased minutely to 1.4% in 2001. A principal reason for concern over occupational segregation is that it is generally seen as an important reason for the continuing differences between the average wages of men and women (Anker, 1998).…”
Section: Occupational Segregation Of Womenmentioning
confidence: 99%
“…Previous research has shown that people with disabilities have lower employment rates than the general population, and that women with disabilities are at a particular disadvantage in the labour market (Achterberg et al, 2009; England, 2003; Fawcett, 2000; O’Hara, 2004; Ren et al, 2008). The entry into the labour market is crucial for young people with disabilities, in that missing the transition from education to employment increases the chances of permanently remaining outside the labour market (Achterberg et al, 2009: 130; Franzén and Kassman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…England (2003) examines gender discrimination and ableism in employment equity, while Momsen (personal communication) is developing a gender atlas for development agencies to target work for women in Bangladesh. Social geographers are also well placed to ensure that the greater emphasis on consultation and participation is more than lip service in government imperatives of listening to communities (Fuller et a., 2003;Pain and Francis, 2003;Burgess, 2005).…”
Section: Introductionmentioning
confidence: 99%